Beyond the Pollen Count: How AI Tools are Revolutionizing Allergy Management - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Allergies, ranging from seasonal rhinitis to life-threatening anaphylaxis, represent a significant and growing global health burden. The World Health Organiz...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation